Social Support as a Predictor of Sexually Abused Adolescents’ Happiness - Hrefna Hrund Erlingsdóttir 1989- (2013)
The aim of the study was to find out whether social support had a buffering effect on the impact of child sexual abuse (CSA) on adolescents‘ happiness.The participants were 7514 secondary school students, 3633 boys and 3744 girls, enrolled in 9th and 10th grade in Iceland in February 2009. Using one-way Anova and logistic regression, the study examined whether social support from parents and friends increased the likelihood of adolescents‘ happiness (main effects) and more so for sexually abused adolescents than those not abused (interaction effects). The results indicated that adolescents with history of CSA were less likely to report being happy. Both social support of friends and parents increased the likelihood of adolescents’ happiness (main effects). However parental support was a weaker predictor of happiness among those adolescents who had experienced intrafamilial abuse whereas friend support was a weaker predictor of happiness for those who had experienced extrafamilial abuse (interaction effects).These results indicate that in general social support of parents and friends is an important predictor of happiness for abused and nonabused adolescents, but in the case of intrafamilial abuse parental support is not as strong predictor of happiness as for other adolescents and in the case of extrafamilial abuse friends support is a less strong predictor of happiness than for others. In conclusion, the results indicate that adolescents who have experience sexual abuse are need more effective social support resources, in particular in the social network surrounding the perpetrator of sexual abuse. Key words: Sexual abuse, social support, happiness